A Matching Model of Crowding-Out and On-the-Job Search (with an Application to Spain) - Juan José Dolado; Marcel Jansen; Juan F. Jimeno (Institute for the Study of Labor (IZA), 2002)
This paper considers a matching model of heterogenous workers and jobs which includes onthe-job search. High-educated workers transitorily accept unskilled jobs and continue to search for skilled jobs. We study the implications of this model for the unemployment rates of high and low-educated workers, for the share of mismatched workers and wage inequality both within and between skill groups. The model is used to shed light on the Spanish experience following a large educational upgrading since the mid-eighties.
Keywords: J62; J41; 330; crowding-out; matching; on-the-job search; unemployment; Arbeitsuche; Crowding out; Arbeitsplatzsuchmodell; Qualifikation; Spanien